Neuronal transcriptomic responses to Japanese encephalitis virus infection with a special focus on chemokine CXCL11 and pattern recognition receptors RIG-1 and MDA5 - Shu, Pin Yu; Kien, Chai Ong; Perera, David; Kum, Thong Wong (Elsevier (New York, Academic Press.), 2018)
Japanese encephalitis virus (JEV) causes central nervous system neuronal injury and inflammation. A clear understanding of neuronal responses to JEV infection remains elusive. Using the Affymetrix array to investigate the transcriptome of infected SK-N-MC cells, 1316 and 2737 dysregulated genes (≥ 2/−2 fold change, P < 0.05) were found at 48 hours post-infection (hpi) and 60 hpi, respectively. The genes were mainly involved in anti-microbial responses, cell signalling, cellular function and maintenance, and cell death and survival. Among the most highly upregulated genes (≥ 10 folds, P < 0.05) were chemokines CCL5, CXCL11, IL8 and CXCL10. The upregulation and expression of CXCL11 were confirmed by qRT-PCR and immunofluorescence. Pathogen recognition receptors retinoic acid-inducible gene-1 (RIG-1) and melanoma differentiation-associated protein 5 (MDA5) were also upregulated. Our results strongly suggest that neuronal cells play a significant role in immunity against JEV. CXCL11, RIG-1 and MDA5 and other cytokines may be important in neuropathogenesis